2020
DOI: 10.1515/opag-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of Ni, Cr, and Si release from alkaline minerals during enhanced weathering

Abstract: AbstractCalcium- and magnesium-rich alkaline silicate minerals, when applied to soil, can aid in carbon dioxide sequestration via enhanced weathering. The weathering of these silicate minerals is also associated with the release of heavy metals such as Ni and Cr, depending on the composition of the parent rock, and also labile Si. This paper critically analyses the risk associated with the release of Ni, Cr, and Si from alkaline silicate minerals as a result of enhanced weather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…One of the key areas of research surrounding the potential of enhanced weathering is the investigation into the build-up of toxic elements in soils and the water column (Renforth, 2012;Hartmann et al, 2013;Renforth et al, 2015;Haque et al, 2020). This potential environmental risk could limit the application of enhanced silicate weathering as a method of carbon sequestration.…”
Section: Heavy Metalsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the key areas of research surrounding the potential of enhanced weathering is the investigation into the build-up of toxic elements in soils and the water column (Renforth, 2012;Hartmann et al, 2013;Renforth et al, 2015;Haque et al, 2020). This potential environmental risk could limit the application of enhanced silicate weathering as a method of carbon sequestration.…”
Section: Heavy Metalsmentioning
confidence: 99%
“…High retention of heavy metals in soils is observed throughout the world in relation to mature soils (Haque et al, 2020), both in secondary minerals (largely clays) and adsorbed. Some laterites have high Ni content (Lewis et al, 2006), with some serpentinite zones showing >2% Ni.…”
Section: Heavy Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In phytoremediation, plants are used to treat soils after they have been contaminated. The existence of these approaches suggests that they could be used preemptively to prevent accumulation and contamination of soils with HM released from TEW (Haque et al, 2020a) -termed "phytoprevention" here. In combination with TEW, this seems a promising approach given that plant species have been identified that (hyper-)accumulate Ni and Cr from soils and waters.…”
Section: "Phytoprevention" Of Heavy Metal Contamination From Tewmentioning
confidence: 99%
“…Moreover, positive growth responses can increase C sequestration in plant biomass if silicates are applied in (semi‐)natural ecosystems where biomass can accumulate (Goll et al, 2021). On the contrary, it might be concerning that ESW is accompanied by the release of heavy metals like Ni and Cr (Beerling et al, 2018; Haque, Chiang, et al, 2020; Hartmann et al, 2013). Nonetheless, the application of Ni is not necessarily problematic and below a certain threshold, Ni may even be beneficial for plants (Ahmad et al, 2011; Kumar et al, 2018).…”
Section: Impact Of Esw On Biotamentioning
confidence: 99%